Pembelajaran Literasi Sejarah Memakai Cerita Pendek - Nugraha, Dipa; Suyitno, Suyitno; Sabardila, Atiqa; Sunanda, Adyana (Stilistika: Jurnal Pendidikan Bahasa dan Sastra, 2025)
Historical literacy learning in Indonesia has developed quite well. Innovative learning has begun to be implemented in historical literacy learning by using interactive applications, films and novels to overcome student boredom. However, existing research shows that historical literacy learning experiences problems with the availability of time when films or novels are used. Meanwhile, the use of short stories in historical literacy learning is not yet commonly implemented in Indonesia. This article, using a literature review, attempts to discuss aspects related to historical literacy learning using short stories. This article also provides three examples of short stories that have the potential to be used in historical literacy learning as an alternative in innovative historical literacy learning. Based on the existing discussion, there are three short stories that can be used in this context, namely “Heiho” by Idrus, “Tamu” by Budi Darma, and “Bapak Presiden yang Terhormat” by Agus Noor.